Factors influencing recruitment and retention of healthcare workers in rural and remote areas in developed and developing countries: an overview - Gisèle Irène Claudine Mbemba; Marie-Pierre Gagnon; Louise Hamelin-Brabant (AOSIS, 2016)
Shortage of healthcare workers in rural and remote areas remains a growing concern both in developed and developing countries. This review aims to synthesize the significant factors impacting healthcare professionals' recruitment and retention in rural and remote areas, and to identify those relevant for developing countries. This paper included the following steps: exploring scientific literature through predetermined criteria and extracting relevant information by two independents reviewers. The AMSTAR tool was used to assess the methodological quality. Of the 224 screened publications, 15 reviews were included. Four reviews focused on recruitment factors, and another four reviews focused on retention factors. The remaining focused both on recruitment and retention factors. The most important factors influencing recruitment were rural background and rural origin, followed by career development. Opportunities for professional advancement, professional support networks and financial incentives were factors impacting retention. While the main factors influencing recruitment and retention have been largely explored in the literature, the evidence on strategies to reduce the shortage of healthcare workers in rural area, particularly in developing countries, is low. Further research in this field is needed.